Bioinformatics analysis of radix Angelica dahurica, Chuanxiong rhizoma, and Cyperi rhizoma for COVID-19 treatment - Hoang, Thi-Van; Nguyen, Chi-Cong; Nguyen, Thi-Thuy-An; Pham, Thi-Thuy-Linh; Nguyen, Phan-Anh; Nguyen, Trang-Thuy; Ha, Hai-Anh (Universitas Islam Indonesia, 2024)
Background: The COVID-19 pandemic, which has unfolded over the past years, poses significant threats to global public health and socioeconomic well-being. Three herbs (radix Angelica dahurica, Chuanxiong rhizoma, and Cyperi rhizoma) have been long utilized in combination for treating common colds and flu.Objective: To analyze potential biotargets and explore possible effects of plant-derived compounds from 3 herbs towards COVID-19 treatment.Method: Bioinformatics databases and network pharmacology were employed to identify bioactive compounds and their biotargets with integrated statistical calculation, followed by Gene Ontology enrichment. KEGG pathway analysis was performed to elucidate the involvement of selected bioactive compounds in COVID-19-related processes.Results: Network pharmacology highlighted essential receptors, cytokines, and signaling proteins. Gene Ontology analysis revealed associations with signal transduction, RNA transcription enzymes, and crucial cellular components. Molecular function analysis emphasized interactions related to virus entry. KEGG analysis uncovered 32 potential targets across various pathways, elucidating their role in inflammation and cytokine storms. Conclusion: This study provides new insight for the molecular mechanisms underlying the therapeutic potential of a combination of radix Angelica dahurica, Chuanxiong rhizoma, and Cyperi rhizoma against COVID-19. The identified targets and pathways offer new directions for further experimental validation, paving the way for potential therapeutic interventions for COVID-19.